2001
DOI: 10.1002/cyto.1131
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal imbalances in primary and metastatic melanomas revealed by comparative genomic hybridization

Abstract: Characteristic genetic changes underlying the metastatic progression of malignant melanoma is incompletely understood. The goal of our study was to explore specific chromosomal alterations associated with the aggressive behavior of this neoplasm. Comparative genomic hybridization was performed to screen and compare genomic imbalances present in primary and metastatic melanomas. Sixteen primary and 12 metastatic specimens were analyzed. We found that the pattern of chromosomal aberrations is similar in the two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
67
0
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 97 publications
(75 citation statements)
references
References 31 publications
7
67
0
1
Order By: Relevance
“…Comparative genomic hybridization (CGH) (Kallioniemi et al, 1992) has proven to be an useful technique for identifying novel regions of amplification. Although CGH studies have revealed a variety of chromosomal aberrations in MM (Bastian et al, 1998;Balazs et al, 2001), only one gene, CCND1, within an amplicon at 11q13, has been identified so far as a target oncogene in acral melanomas (Sauter et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Comparative genomic hybridization (CGH) (Kallioniemi et al, 1992) has proven to be an useful technique for identifying novel regions of amplification. Although CGH studies have revealed a variety of chromosomal aberrations in MM (Bastian et al, 1998;Balazs et al, 2001), only one gene, CCND1, within an amplicon at 11q13, has been identified so far as a target oncogene in acral melanomas (Sauter et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Imprint preparations were made from fresh or frozen tissues and fixed as described previously (29). Six-micron sections were stained with hematoxylin and eosin for morphologic examination.…”
Section: Materials and Methods Tumor Samples And Histopathologic Datamentioning
confidence: 99%
“…CGH experiments were carried out as described previously (29). Briefly, the hybridization mixture, consisting of 200 ng of each labeled DNA and 20 mg of unlabeled human Cot-1 DNA (Life Technologies, Gaithersburg, MD, USA), was precipitated and dissolved in hybridization mixture and denatured at 73°C (3-5 min) immediately before applying onto normal metaphase spreads (Vysis Inc.).…”
Section: Comparative Genomic Hybridizationmentioning
confidence: 99%
See 2 more Smart Citations